Promoting Climate Change Adaptation Measures for Improving Productivity among Smallholder Farmers in Taraba State, Nigeria - E.N, Mbah; A.I, Onwusika; M.N, Okeke (International Journal of Climate Research, 2017)
The study assessed promoting climate change adaptation measures for improving productivity among smallholder farmers in Taraba State, Nigeria. Interview schedule/questionnaire was used to collect data from a sample of ninety (90) respondents used for the study. Data were analyzed using factor analysis. Findings indicate that major effects of climate change among smallholder farmers were named based on the items loading for factors 1, 2 and 3 as food security, poor quality of produce and soil conservation effects, respectively. Factor analysis of variables with regards to climate change adaptation measures practiced by smallholder farmers based on the item loadings were named factors 1, 2 and 3 (agronomic practices, farm inputs and production measures, respectively). Variables which loaded high under agronomic practices include practicing of mulching (0.776), planting early maturing varieties of crops (0.643), early harvesting of matured crops (0.604) and adjustment of planting dates (0.542). Loadings under farm inputs were planting of cover crops to reduce loss of water from the soil (0.794), use of organic manure (0.794), practicing bush fallowing to increase soil fertility (0.743) and planting of improved varieties of crops (0.630). Production measures comprised value addition of farm produce (0.647), use of high yielding varieties of crops (0.630), practicing mixed cropping to guard against crop failure (0.577), practicing zero tillage (0.472) and erection of dams for storing water (0.464). Constraints to climate change adaptation measures among smallholder farmers were grouped into infrastructural, labour and fund-related problems. Efforts are highly needed in cushioning the effects of climate change by the stakeholders such as the government at all levels, extension agencies, research institutions, metrological institutes, disaster management agencies, higher institutions, local farmers and others by giving out first hand information on weather forecast so as to know the right and best time to plant and harvest crops. It also highlights the need for provision of adequate infrastructure to enhance easy adaptation to climate change as well as increasing productivity.